The Effect of Premedication on the Incidence of Gastroesophageal Reflux in 270 Dogs Undergoing General Anesthesia - Eugenia S. Flouraki; Ioannis Savvas; George Kazakos; Tilemahos Anagnostou; Dimitrios Raptopoulos (Animals, 2022)
The aim of this prospective, non-randomized study was to evaluate the effect of nine different premedication medications on the incidence of gastroesophageal reflux (GOR) in anesthetized dogs. Two hundred and seventy dogs undergoing non-intrathoracic, non-intrabdominal elective surgeries or invasive diagnostic procedures were included in the study, and were allocated into nine groups (30 dogs/group) defined by the type of premedication administered. Premedication consisted of dexmedetomidine with either morphine, pethidine or butorphanol, acepromazine with either one of the three opioids or midazolam with one of the above-mentioned opioids. Anesthesia was induced with propofol and maintained with isoflurane in oxygen. Esophageal pH was measured with the use of a pH-meter electrode and a pH-value less than 4 and over 7.5 was considered to be GOR. The study revealed that 119/270 (44.1%) dogs experienced a reflux episode during anesthesia. The incidence of reflux did not differ among groups (p = 0.117). In group AB the dogs refluxed within 10 min of the beginning of pH-measurements, in comparison with group DB in which dogs refluxed within 30 min (p = 0.029). Invasive diagnostic procedures had a lower incidence of GOR in comparison to castrations (p = 0.09). The outcome of the study suggests that none of the opioids used increased the incidence of GOR in anesthetized dogs.